The flora, vegetation, and conservation value of mesic forest at Dogotuki, Vanua Levu, Fiji Islands - Keppel, Gunnar; Rounds, I.; Thomas, N. (Taylor & Francis Australasia, 2006)
The flora and vegetation of an area in north-eastern Vanua Levu that is part of Fiji's last major system of mesic forest were studied and revealed a mosaic of vegetation types, including mesic sclerophyll forest, transition forest, stunted Dacrydium nidulum forest, mangrove forest, montane forest, brackish and freshwater wetlands, and disturbed landscapes. This is much more diverse than indicated by the previous “dry forest” label. The flora comprises more than 268 native species, several of which are rare or narrowly distributed. Relatively large and undisturbed stretches of vegetation and the presence of rare and novel species and vegetation types suggest that the landowners should be given every possible assistance in protecting this unique landscape.